Perceptions and Implications of Herdsmen and Farmer's Bloody Clashes on Sustainability and Economic Growth in Nigeria: Investigative Journalism Approach - Edih University Ovuokeroye; UmuzeNkechi Anthonia; University Ebitare Esther (Britain International for Academic Research (BIAR-Publisher), 2022)
This study examined the perceptions and implications of herdsmen and farmers bloody clashes on sustainability and economic growth in Nigeria; investigative journalism approach. The study employed a cross-sectional survey and qualitative research design in which 1000persons were interviewed to seek their perceptions on the effects of the feud. It was revealed that no party is happy with the irreparable consequences that ensued from the clash. It was shown that the herdsmen were misguided on the grazing routes which the Federal government insists on reviving or re-enacting when such routes or policy cannot be operational due to increasing human population, mechanized/commercial agricultural activities in modern days. The clash was also induced by born to rule ego, religious inclinations and mutual distrust. It does implies that persisting violence is a precursor to hunger/malnutrition, high cost of living, economic recession, civil war and disintegration of a volatile country. The crisis is persisting due to the lackadaisical/double standards attitude of government towards resolving the impasse on time. It has been seen that open grazing cannot continue in modern Nigeria. It has to be stopped for the implementation of ranching programmes. Government should intensify laws against criminality/ cattle rustlers and disarm both farmers-herdsmen of the arms they are parading everywhere. The constitutional role of government is to ensure that the rule of law prevails equally over all citizens in whatever trade, religion/ethnic background. There should be intensive media sensitisation on inter- ethnic and inter-religious tolerance and harmony in the country.